Antibiotic Discontinuation at Clinical Resolution Versus Seven Additional Days for Canine Superficial Pyoderma: A Randomized Clinical Study - Jennifer L. Clegg; Clarissa P. Souza; Sheila M. F. Torres (Veterinary Sciences, 2026)
The primary objective of this study was to determine if superficial pyoderma (SP) recurs sooner and at a higher rate in dogs not treated beyond clinical resolution. Sixty-seven client-owned dogs were randomly assigned to either group A (n = 37), treated with a culture-based oral antimicrobial for seven days beyond resolution, or to group B (n = 30), treated until resolution. After withdrawals, 60 dogs were analyzed for SP resolution. Dogs were examined every 14 days until D98, unless excluded due to unresolved SP by D42 or if SP recurred before D98. At each visit, a dermatologic exam and pyoderma severity score determination (0–21) were performed. Clinical resolution of SP was observed in 28 days (median) in 20/33 dogs in group A and in 18/27 in group B and not observed by D42 in 13/33 dogs in group A and 9/27 in group B. These dogs were considered treatment failures. SP recurred in 13/20 dogs in group A and 10/18 in group B after 67.5 days and 69 days (median) of follow-up time in group A and B, respectively. The median follow-up time to SP recurrence was 67.5 days and 69 days in group A and B, respectively. The hazard ratio for the risk of SP recurrence in group A compared to group B was 1.04 (95% CI 0.42–2.66; p = 0.9319). In this sample, there was no statistically significant difference between the groups for pyoderma score, resistance patterns, time to SP resolution, time to recurrence, recurrence rate, or probability of recurrence. Extending antibiotics seven days beyond clinical resolution is not necessary for canine SP treatment.